Targeting Autophagy with Natural Compounds in Cancer: A Renewed Perspective from Molecular Mechanisms to Targeted Therapy - Qiang Xie; Yi Chen; Huidan Tan; Bo Liu; Ling-Li Zheng; Yandong Mu (Frontiers Media S.A., 2021)
Natural products are well-characterized to have pharmacological or biological activities that can be of therapeutic benefits for cancer therapy, which also provide an important source of inspiration for discovery of potential novel small-molecule drugs. In the past three decades, accumulating evidence has revealed that natural products can modulate a series of key autophagic signaling pathways and display therapeutic effects in different types of human cancers. In this review, we focus on summarizing some representative natural active compounds, mainly including curcumin, resveratrol, paclitaxel, Bufalin, and Ursolic acid that may ultimately trigger cancer cell death through the regulation of some key autophagic signaling pathways, such as RAS-RAF-MEK-ERK, PI3K-AKT-mTOR, AMPK, ULK1, Beclin-1, Atg5 and p53. Taken together, these inspiring findings would shed light on exploiting more natural compounds as candidate small-molecule drugs, by targeting the crucial pathways of autophagy for the future cancer therapy.